Pedagogical Studies in the Framework of Cultural Literacy Skills at School : Observation of Labschool UPI Junior High School and Kartika XIX-2 Junior High School - Eka Yuliana Rahman (IAIN Manado, 2023)
In the school environment, understanding culture is also important. Every generation changes with its challenges. Multiple intelligence can be an approach in understanding students. Observations in two private schools were carried out with the aim of seeing the extent and form of cultural literacy carried out in private schools. Pedagogical studies in the frame of cultural literacy as an effort to maintain the local heritage that exists in the West Javanese community in Bandung City, especially kasundaan. Two schools that are carried out the observation process, namely UPI Lab School and SMP Kartika XIX-2 in carrying out the learning process also pay attention to environmental factors that shape the character of students. The results showed that cultural literacy was carried out by teachers and the school environment with a variety of approaches and even through learning resources. The results of this study also found that the activities took place, students followed them enthusiastically, despite the degradation of understanding of Sundanese and the limited Sundanese culture that was deeply understood by students. Further research is needed to see how far the results or impact felt by students after the implementation of cultural literacy carried out by the school.